The microbiome during pregnancy and early postnatal life. Issue 6 (December 2016) - Neu, Josef
Summary: We are changing our concept that the newborn infant emerges from a sterile environment. In-utero colonization may have major impacts on the developing mammal in terms of development of immunity and metabolism that, with epigenetic modifications, will lead to diseases in later life. In addition, the microbial profile that develops during and after birth depends on mode of delivery, type of feeding (human milk versus formula) and various other environmental factors to which the newborn is exposed. The goal of this review is to clarify that the microbiome in the maternal fetal unit as well as the immediate changes that occur as new microbes are acquired postnatally play major roles in subsequent health and disease. Rapidly developing technologies for multi-omic analyses and systems biology are shifting paradigms in both scientific knowledge and clinical care.